(untitled) (ETIMA, 2021)
Abstract With the fickle nature of the weather conditions upon which renewable energy sources mostly depend, as well as the changing consumer demand profile, the need for balance in the electric power system between supply and demand through a reliable energy storage system becomes essential. Besides most of the energy storage system technologies are not commercially viable at present due to some of their limitations, the battery energy storage system (BESS) carries out an increased role and frequency in energy markets and continuous improvements that serve a variety of energy optimization purposes, improving the quality, reliability, and affordability of electricity. This topic covers and analyzes the different technologies of the battery system and their characteristics according to the type of battery, their adaptation, evolution, and functionality as key to the energy transition. Flexible options are necessary to overcome the overall variability between the interaction of systems and the regulation of their parameters. The battery energy storage system cannot become obsolete in the coming period, but on the contrary will contribute to faster realization of new energy trends, development of stationary markets, and the rise of a sustainable energy future. Keywords: energy transformation, renewable energy, battery technologies, grid-level energy storage, energy sector trends, electrochemical design, battery model